(untitled) (Asian Journal of Pharmaceutics (AJP), 2017)
Purpose: This study was aimed to evaluate the caries activity in children with acute lymphoblastic leukemia (ALL) undergoing maintenance stage chemotherapy courses. Materials and Methods: This is an observational-analytical and case-control study conducted on the 27 children (4-12 years old) with ALL who were in the maintenance phase of chemotherapy in the Ahvaz Shafa Hospital, Iran. The participants of the control group, matched in terms of age, gender, and cultural status with the case group, were selected among the healthy children referred to Ahvaz Razi Hospital, Iran. The children received only a clinical dental examination without radiographs. The number of decayed (D), missing (M) and filled (F), and teeth (T) were recorded based on the WHO based DMFT index and without the use of radiography. Then, after radiographic assessment, the stimulated saliva samples were collected from the subjects to assess the salivary Streptococcus mutans counts, salivary Lactobacilli counts, and salivary buffer capacity. Results: The salivary S. mutans counts in ALL children were significantly higher than the control group (P < 0.001). In both groups, Lactobacilli counts and salivary pH and DMFT were similar (P > 0.05). Furthermore, the ALL group tended to have lower salivary flow rate than healthy subjects (P < 0.05). Conclusions: Specific oral prevention regimes should be planned with more cautions for children suffered hematology illness undergoing antineoplastic therapy with respect to children without blood problems